Investigação das características da memória autobiográfica relacionadas a regulação emocional de adultos - Cardoso Filho, Valfrêdo Felinto (2019)
The possible relationships between the processes of emotional regulation and autobiographical memory retrieval have been the subject of discussion in the literature, seeking to understand which of the processes would be having an effect on the other. Emotional regulation describes cognitive strategies that regulate the intensity and expressiveness of emotion, while autobiographical memory refers to life story events. The objective of this study was to analyze the possible relationships between the characteristics of these constructs to broaden the data in this debate framework. The sample included 16 women and 14 men aged between 20 and 30 years, college students, without depressive and anxious symptoms and no psychiatric diagnosis. The instruments used were: the Autobiographical Memory Test (TMA), the Self-Assessment Manikin Scales (SAM), the Autobiographical Memory Questionnaire (QMA), the Emotional Regulation Questionnaire (QRE) and the Emotional Regulation Difficulty Scale (EDRE). Results indicate that healthy adults, men and women, who make predominant use of cognitive reevaluation as an emotional regulation strategy, recover more specific than general autobiographical memories, with no difference between positive emotional valence and negative memories. The study contributed to understand the importance of the recovery of autobiographical memories and their respective emotional responses to personal life.